Peptic ulcer and intestinal metaplasia associated with Helicobacter pylori colonization in gastric heterotopia of the tongue - Ufuk Berber; İsmail Yılmaz and Bülent Evren Erkul and Mustafa Kaplan (Turkish Journal of Gastroenterology, 2019)
-